An Optimal Data Access Framework For Telerehabilitation System - Abdullah Muhammed; Siti Nabilah Basarang; Ali Y. Aldailamy; Rimuljo Hendradi; Waidah Ismail (Faculty of Information and Communication Technology (FTMK), Universiti Teknikal Malaysia Melaka (UTeM)., 2024)
Vol: 3 No: 1 (page: 25-36)